Gitano, na. Contextualised history of an entry in the Spanish Royal Academy's lexicography - Buzek, Ivo (Romanica Olomucensia, 2016)
The aim of the paper is an analysis of the evolution of the entry gitano, na [Gypsy] in the Spanish Royal Academy's lexicographic tradition. Attention will be paid to the evolution of its lexicographic treatment and its correspondence to available textual documentation in the Academic corpora (CORDE, CDH, CREA, CORPES XXI and Fichero General) in order to see whether or not the Academy's dictionaries could serve as social dictionaries for the Spanish-speaking world and what kind of ideology they transmit to speakers of Spanish.
Keywords: Gypsy; Spanish Royal Academy's dictionaries; social lexicography; textual documentation; ideology.